Analisis Perbandingan Penegakan Hukum Tindak Pidana Kecelakan Lalu Lintas oleh Anak di Indonesia dan Malaysia - Surachman, Vitriyah Arafah; Susanti, Rahtami; Kamarudin, Shah (Proceedings Series on Social Sciences & Humanities, 2024)
The number of traffic violations and accidents by children in Indonesia and Malaysia is quite high as evidenced by the many cases that have occurred in both countries, giving rise to debates about the regulation and application of law enforcement of traffic accidents by children in both countries. Law enforcement is a whole series of actions to maintain and maintain the balance of rights and obligations of citizens in accordance with human dignity and dignity, as well as their respective responsibilities according to their functions fairly and equally. This research aims to compare the regulation and law enforcement of criminal traffic accidents by children in Indonesia and Malaysia. The research method is normative juridical with statute approach and comparative approach. The data used is secondary data and analyzed descriptively qualitative. The data collection technique used in this research is library research. The result of the research is that criminal responsibility for traffic accidents by children in Indonesia already has an integrated arrangement with Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak through the practice of diversion and restorative justice approaches. Whereas in Malaysia, there is no integration of legal arrangements specifically related to law enforcement of criminal traffic accidents by children. There are only rules regarding child driver traffic accidents in Sections 39 of the Road Transport Act 1987 (Act 333) and rules regarding the age limit of child criminal liability through the Kanak-Kanak Act 2001 (Act 611) and the Malaysia Penal Code.